MEWUJUDKANGOOD GOVERNANCEMELALUI E-PROCUREMENT - Nurul Rofikoh; As Martadani Noor (JIANA ( Jurnal Ilmu Administrasi Negara ), 2013)
The processofpublicprocurementisthelargestcontributortothepracticeofCorruption,CollusionandNepotism(KKN) in thepublicbureaucracyinIndonesia, both atthe centralandlocalgovernments. It happened because the conventional procurement system has a number ofweaknesses that allow corrupt practices in each stage.The research aim to provide an overview of theweaknesses of conventional procurement and the importance of applying the principles of goodgovernance in the public procurement, through the mechanism of procurement of goods and serviceselectronically (e-procurement).Data were collected through literature review, secondary data andfocus groupdiscussions and analyzed by the technique of triangulation.The results showed that e-procurement system has many advantages over conventional auction them more efficient , effective ,transparent , accountable , fairer and safer and can bring a healthy competition of business actors .With e -procurement opportunities for direct contact between the supplier of goods / services with theprocurement committee becomes smaller , more transparent , more efficient time and cost as well aseasy to do in practice financial accountability , so that corruption and collusion can be avoided .Key words: e-procurement, good governance, public bureaucracy, public services.